Model Partisipasi Orangtua Siswa dalam Penyelenggaraan Pendidikan di KB TK Labschool Jakarta - Vany Vindri Permata; Rugaiyah; Masduki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe and analyze the model of parental participation in the implementation of education at KB TK Labschool Jakarta. Parental involvement is one of the key supporting factors in the success of early childhood education. This research employs a qualitative approach with a case study design. Data collection techniques include observation, in-depth interviews, and documentation. The findings indicate that parental participation at KB TK Labschool Jakarta encompasses academic, non-academic, and decision-making aspects. The participation model developed emphasizes active collaboration between the school and parents through open communication, involvement in school activities, and regular evaluation forums. The study concludes that active and structured parental involvement has a positive impact on the quality of early childhood education implementation.